The Complexity of Modern Relationships: A Representation of Situationship in Music Album - Muchtar, Moch. Shobastian Mahendra (Tuturlogi: Journal of Southeast Asian Communication, 2026)
This study explores the representation of situationships—ambiguous romantic relationships lacking clear commitment—in Ariana Grande's album Eternal Sunshine, using Robert Sternberg's Triangular Theory of Love as a framework. Situationships, characterized by emotional intimacy and passion but low commitment, reflect the complexities of modern romantic dynamics. Through qualitative content analysis of 13 songs, the research identifies themes of intimacy, passion, and commitment, revealing how Ariana's lyrics depict the emotional struggles and communication challenges inherent in such relationships. The findings highlight the tension between emotional closeness and the absence of commitment, leading to instability and dissatisfaction. The study underscores the importance of effective interpersonal communication in navigating ambiguous relationships and emphasizes music as a powerful medium for reflecting contemporary relational dynamics. By integrating theoretical and cultural perspectives, this research contributes to understanding the emotional and communicative complexities of modern love, offering insights into the role of music in articulating the nuances of romantic relationships.